Pengaruh Kesadaran Nilai, Integritas, Gratifikasi Personal, dan Penghindaran Risiko terhadap Sikap dan Perilaku pada Produk Lagu Bajakan - Sony Kusumasondjaja; Syahrial Ashari (Jurnal Manajemen dan Bisnis Indonesia, 2014)
The increasing adoption of pirated music products in Indonesia intesifies the needs to understand factors influecing consumers to buy pirated music products. This study examines the impact of value consciousness, personal integrity, risk avoidance, and personal gratification on consumer attitude toward pirated music products and their intention to buy the products. Data was collected through mall-intercept survey distributed on several music concerts involving 150 music lovers. Findings suggest that consumers who are aware of product value tend to have favorable attitued and intention toward pirated music products, meanwhile consumers whose high level of personal integrity, risk avoidance, and personal gratification also have positive attitude and intention toward the pirated music products. Research contributions and implications are also discussed. Kata Kunci: kesadaran nilai, risiko, sikap, niat konsumen, online marketing